Resisting Unmet Expectations as Service User Ethics: Implications for Social Work. Issue 3 (2nd September 2021) - de Bie, Alise; Daley, Andrea; Ross, Lori E.; Kidd, Sean A.
ABSTRACT: This paper takes up a call from activists and scholars in Mad and Disability Studies to pay more explicit attention to resistance. Drawing on conceptualizations of predictive, normative, and ideal expectations, we describe three ways 2SLGBTQ service users who have experienced psychosis resist unmet expectations of just treatment. These include: (1) defending self-respect through resistant thinking and resentment; (2) reducing discrepancy through lowering expectations of just treatment from others; (3) and protecting selves through distrust and self-reliance. This paper makes several contributions to existing literature: It expands our understanding of the 'everyday' forms of resistance that service users engage in, particularly those that are 'quiet' and risk being missed. By paying attention to quiet forms of resistance, we come to recognize the everyday 'moral talk' of service users, and opportunities for collectivizing the values underpinning this talk into ethics. Supporting the creation and affirmation of these ethics is one way for social work to address the exclusion of service users from the creation of social work ethical guidelines and respect and acknowledge the legitimacy of service user knowledges, especially their developing visions of justice and moral relations.